Mortality and Morbidity of Surgical Management of Geriatric Ankle Fractures. Issue 16 (15th August 2020) - Gil, Joseph A.; Goodman, Avi D.; Kleiner, Justin; Walsh, Devin F.; Kosinski, Lindsay R.; Hsu, Raymond
Abstract : Introduction: The incidence of geriatric ankle fractures is rising. With the substantial variation in the physiologic and functional status within this age group, our null hypothesis was that mortality and complications of open reduction and internal fixation (ORIF) between patients who are aged 65 to 79 are equivalent to ORIF in patients who are aged 80 to 89. Methods: Patients with ankle fracture were identified using the International Classification of Diseases, Ninth Revision, Clinical Modification diagnosis codes. Patients treated with ORIF were identified using the Current Procedural Terminology codes. Patients were divided into two age cohorts: 65 to 79 years of age and 80 to 89 years of age. The primary outcome studied was 30-day mortality. Secondary outcomes included 30-day readmission, revision surgery, surgical site infection, sepsis, wound dehiscence, pulmonary embolism, deep vein thrombosis, blood transfusion, urinary tract infection, pneumonia, stroke, myocardial infarction, renal insufficiency or failure, and length of hospital stay. Results: Our cohort included 2, 353 ankle fractures: 1, 877 were among 65 to 79 years of age and 476 were among 80 or older. Thirty-day mortality was 3.2-fold higher in the 80 to 89 years of age group compared with the 65 to 79 years of age group (1.47% versus 0.48%, P = 0.019). However, after controlling for the ASA class, 80 to 89 years of age patients no longer had a significantly higher mortality ( P = 0.0647). Similarly, revision surgery rate (3.36% versus 1.81%, P = 0.036), transfusion requirement (2.94% versus 1.49%, P = 0.033), urinary tract infection (1.89% versus 0.75%, P = 0.023), and hospital length of stay (4.9 versus 2.9 days, P < 0.0001) were all significantly higher in the 80 to 90 years of age group compared with the 65 to 79 years old group. However, after controlling for the ASA class, 80 to 89 years old patients no longer had a rate of complications in comparison to the 65 to 79 years old age group. Discussion: After controlling for comorbidities (ie, the ASA class), no increased risk is observed for the 30-day mortality or complication rate between geriatric ankle fracture in the 65 to 79 years old and the 80 to 99 years old age groups. Level of Evidence: Prognostic level III, retrospective study.